A review on egg waste-based adsorbents for the removal of organic and inorganic contaminants from aqueous solution - Alusani Manyatshe; Linda Lunga Sibali (Heliyon)
Converting biomass waste into valuable products has recently gained popularity among scientists worldwide. The potential of egg biomass waste as an adsorbent for removing organic and inorganic contaminants from aqueous solutions has been investigated. This review paper assessed the techniques of developing egg waste adsorbents, physicochemical characteristics, and mechanisms underlying the adsorption of pollutants. Calcination and pyrolysis were the predominant methods to modify raw eggshells. Meanwhile, chemical methods were often employed to modify raw eggshell membranes. Characterisation techniques showed that the raw eggshells and membranes consisted mainly of calcium carbonate (CaCO3) and proteins (amine and carboxylic groups). Most studies have focused on using adsorbents based on eggshells to remove various contaminants, including dyes, phenols, aromatic carbons, anions, metals, and pharmaceuticals. In contrast, the eggshell membrane was mainly investigated for removing metals and dyes, with little to no research on phenols, aromatic carbons, and pharmaceuticals. The precipitation, ion exchange, and electrostatic attraction dominated the adsorption mechanism between the egg waste-based adsorbents. Moreover, while adsorbents made from pure egg waste have demonstrated some efficacy in removing contaminants, modifying the eggshell and eggshell membrane has proven crucial in enhancing the adsorbent's effectiveness. Additionally, most of the research has been conducted on synthetic wastewater; therefore, future studies should concentrate on testing adsorbents in natural wastewater, pilot scaling, and calculating the economic cost, as this would move technology closer to commercialisation. Nonetheless, egg waste adsorbents have demonstrated the potential to be employed as sustainable, low-cost materials to remove contaminants from aqueous solution.